(3GdJLQHI GdjGHGfjI aj GdGOGQI hGdJfXjes (3GdOYGFe GdGSGSjI hebheGJ GdfLGMs - (3GHh bMa(B, (3YHO GdSdGes ((3GdGScfOQjIs (3GdecJH GdYQHj GdMOjKs, 1998)
(3aj gPG GdcJGH (B: (3GdfXGe GdGOGQi hOYGFeI Ydi eSJhi GdOhdI GdfXGe GdGOGQj(B: (3GdNUGFU h GdSeGJ h GdOYGFe GdGSGSjI h GdGSJKeGQGJ , GdedGeM h GdeMGhQ GdGSGSjI dfXe GdGOGQI h GdJfXje, GdGfJGLjI h GSHGH GdfLGM aj GdeUGfY h GdTQcGJ, HYV GdeeGQSGJ GdGOGQjIs
Keywords: (3GdGOGQIs